Tingkat pengetahuan siswa tentang pembelajaran renang kelas VII di SMPN 1 Banyusari Kabupaten Karawang - Aprizal, Muhamad; Nasution, Nana Suryana; Sumarno, Ardawi; Fauzi, Dira (Jurnal Porkes, 2024)
This study aims to assess the level of student knowledge about swimming lessons. The research method uses a survey method with a questionnaire. Based on the results of the study, the level of student knowledge about swimming lessons is in the "good" category by getting an average score (mean) of 22 from all data taken according to the assessment reference norm. Based on indicators of the level of student knowledge about swimming learning which has 3 categories including swimming techniques, swimming rules and knowledge, facilities and infrastructure. Students have good knowledge based on several indicators or factors regarding "swimming techniques" by 37%, "swimming rules and knowledge" by 32%, "swimming facilities and infrastructure" by 31%, then for the level of student knowledge about swimming learning has a higher level of knowledge based on the indicator "swimming techniques" by 37% because it is more dominant than other indicators. It is concluded that the level of knowledge of students about swimming lessons is included in the "good" category.